OPTIMISING THE QUALITY OF SCHOOL WORK PROGRAM IN IMPROVING STUDENTS' PERSONALITY COMPETENCE: A CASE STUDY AT AL AZHAR ISLAMIC JUNIOR HIGH SCHOOLS 6 AND 9 BEKASI - Hasim, Ismail; Komara, Endang; Hidayat, Hidayat; Mulyanto, Agus (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Education in Indonesia faces serious challenges related to quality and equity, as shown by its low global ranking. This research focuses on optimising the quality of school work programs as an effort to improve students' personality competencies at Al Azhar 6 and 9 Bekasi Islamic Junior High Schools, emphasising the importance of character education in the context of formal education. Using a descriptive qualitative approach, data were collected through semi-structured interviews, direct observation and document analysis, and participants were purposively selected to explore in-depth information about the implementation of the school work programme. The results showed that structured planning and organisation of the work program contributed significantly to improving teachers' personality competence and student enrolment stability, while continuous implementation, control and evaluation supported improved students' academic and non-academic achievements. The findings support the importance of collaboration between principals, teachers and parents and the use of technology and SMART methods in planning, although there are limitations related to the scope of participants and the subjectivity of the data collected, so further research is needed to extend the generalisability of the results.